Identifying oral macula with malignant potential and its etiology: A case report with literature review - Rasdayanti, Nur; Usman, Nur A.; Sumintarti, Sumintarti; Harlina, Harlina; Yusran, Ali; Marlina, Erni; Putri, Andi AM. (Hasanuddin University, 2024)
Objective: This article aims to report interesting case of whole mouth pigmentation, including on patient full protheses.Methods: A 79-year old female came to dental clinic with a chief complaint of difficulty in swallowing. The patient felt no pain but is very uncomfortable due to impaired taste and a burning sensation in her mouth. In addition, the patient's dentures were stained with a diffuse black-and-white coating indicating a long and chronic course event. This complaint occurred for last 2 months, after a long history of being in and out from the hospital due to several illnesses. Ongoing treatment of the patient include drug for chronic digestive diseases and hypertension. Results: The patients told to come back in 7 days with strict instructions to bring all hospital-related documents to rule out possible etiologic of the pigmentation.Conclusions: This interesting case concluded with working diagnosis of oral melanocarcinoma due to macula fast and massive spread and distribution. However, black-pigmentation on patient prothesis can lead to a strong suggestion that the trigger of those malignant possible triggered by a long-chronic un-treated candida infection.